GIS Day across the Association of Research Libraries: Outreach, Education, and Collaboration. Issue 3 (1st September 2020) - Sadvari, Joshua; Koshoffer, Amy; Gorham, R. Benjamin; Phillips, Katie
ABSTRACT: GIS Day is an annual, international celebration of geographic information systems (GIS) and geospatial technologies that provides organizations with an opportunity to help others learn about the real-world applications and positive societal impacts of geography and GIS, highlight services, and celebrate accomplishments. Many academic libraries participate in GIS Day programs, using this well-known event to engage with their campus and local communities. In this article, we build on earlier research conducted by Weimer, Olivares, and Bedenbaugh to reassess the landscape of Association of Research Libraries (ARL) member involvement in GIS Day programs and, in particular, how these events demonstrate the educational and collaborative aspects of geospatial information services in libraries. For our web content analysis, we specifically focus on gathering information about GIS Day programs in 2019 and 2020, allowing for an examination of how libraries participating in GIS Day responded to the operational challenges posed by the COVID-19 pandemic, as well as new opportunities that may have emerged during this period. Finally, we offer our own 2020 GIS Day program as a brief example highlighting how it led to our first cross-institutional collaboration and fostered new opportunities for promoting and partnering on digital scholarship projects at our institutions.